Implementation Color Filtering and Harris Corner Method on Pattern Recognition System - Ahmad Zarkasi; Sutarno Sutarno; Huda Ubaya; Muhammad Fajar (Computer Engineering and Applications Journal, 2017)
Color recognition and angle detection of underwater objects can be done with the help of underwater robots (ROV) with image processing applications. The processing of the object's image is recognizing various shapes and colors of objects in the water. In this research, the color filtering and Harris corner method will be designed, studied, tested and implemented. The color filtering method is used to recognize object color patterns, while the Harris Corner method is used to detect angles of underwater objects. Then classify images to get data on environmental pattern recognition. The color patterns tested include red, green, yellow and blue. the results obtained are all color patterns can be recognized well. while the shape of the object being tested includes cubes, triangles, rectangles, pentagons, and hexagons. the results of testing some of the shapes can be detected with a good angle and others still have errors. This is because testing the form of objects is done in various positions, such as from the front, right, left, up and below.Â